Long term results after transpupillary thermotherapy in eyes with occult choroidal neovascularisation associated with age related macular degeneration: a prospective trial. Issue 2 (19th January 2006) - Stolba, U; Krebs, I; Lamar, P D; Aggermann, T; Gruber, D; Binder, S
Abstract : Aim: To evaluate long term results after transpupillary thermotherapy (TTT) in eyes with exudative age related macular degeneration. Methods: In a prospective clinical study eyes with occult or predominantly occult choroidal neovascularisation and no pretreatment were scheduled to have a TTT with a power of 630 mW. Visual acuity for far and near distances as well as contrast sensitivity were evaluated 6, 12, and 24 months postoperatively and statistically analysed. Results: 47 eyes fulfilled the inclusion criteria. Overall, 70% of the patients showed an improved (14%) or had unchanged (56%) ETDRS vision after 24 months. Reading vision was stabilised (51%) or better (5%) in 56% of the eyes at this time. However, the increasing number of eyes with severe deterioration resulted in a significant decrease of both parameters over time (p = 0.0002 and p = 0.0003, respectively). Contrast sensitivity could be maintained (70%) or improved (9%) in 79%. Statistical analyses indicated a trend but no significant decrease over time (p = 0.056). Conclusion: Although in the majority of patients far and near distance acuity could be stabilised on average a significant decrease over time after TTT was observed. Statistical comparison of months 12 and 24 showed no further deterioration.